Education and Peacebuilding: Cultural Values as the Foundation for Conflict Resolution in Schools - Afdhal, Afdhal (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Schools in Maluku often face social conflicts rooted in religious, ethnic, and historical local tensions, which have the potential to disrupt the learning process and create an unconducive environment. The main issue at hand is how to foster a harmonious and peaceful atmosphere among students in such a situation. This study aims to analyze the role of local cultural values as a foundation for conflict resolution in schools, supporting education and peacebuilding. The study uses a qualitative method with observations and in-depth interviews in several schools in Maluku. The findings show that cultural values such as Pela, Gandong, and Masohi play a crucial role in fostering tolerance and peace among students. Pela and Gandong serve as symbols of inter-religious and inter-regional brotherhood, which are internalized through collaborative activities among students, while Masohi, which emphasizes mutual cooperation, is applied in project-based learning and community activities, promoting collaboration and empathy. These findings highlight the importance of integrating local cultural values as a hidden curriculum in shaping tolerant student characters and creating a school environment that sustainably supports peacebuilding.